2010
DOI: 10.1007/s10712-010-9100-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved Constraints on Models of Glacial Isostatic Adjustment: A Review of the Contribution of Ground-Based Geodetic Observations

Abstract: The provision of accurate models of Glacial Isostatic Adjustment (GIA) is presently a priority need in climate studies, largely due to the potential of the Gravity Recovery and Climate Experiment (GRACE) data to be used to determine accurate and continent-wide assessments of ice mass change and hydrology. However, modelled GIA is 123Surv Geophys (2010) 31:465-507 DOI 10.1007/s10712-010-9100-4 uncertain due to insufficient constraints on our knowledge of past glacial changes and to large simplifications in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 148 publications
(213 reference statements)
3
89
0
1
Order By: Relevance
“…Recent efforts that will help to reduce the current GIA uncertainty include for instance the use of space-geodesy (e.g. King et al 2010). …”
Section: Discussion Of Contributions Included In This Studymentioning
confidence: 99%
“…Recent efforts that will help to reduce the current GIA uncertainty include for instance the use of space-geodesy (e.g. King et al 2010). …”
Section: Discussion Of Contributions Included In This Studymentioning
confidence: 99%
“…They showed that the effect of including or not including an annual signal in the time-series analysis, is much larger when a power-law plus white noise model is used instead of a pure white noise model. Teferle et al (2009) argue that annual and semi-annual signals can bias the velocity In King et al (2010) theoretical vertical site velocity uncertainties for stations in the Northern Hemisphere of 1.41, 1.58 and 0.54 mm/year after 5 years of observations and 0.71, 0.79, 0.27 mm/year after 10 years of observations are derived using DD, Precise Point Positioning (PPP) and regional stacking, respectively. The uncertainties in the horizontal components are between a third and a fourth in the Double Difference (DD) solution and between half and a third in the Precise Point Positioning (PPP) solution.…”
Section: Discussion On Time-series Analysis and Time-series Lengthmentioning
confidence: 99%
“…That is, systematical errors in the reference frame realization, errors in the GNSS analysis strategy or local secular motion of the antenna monument may also affect our velocity solutions (see e.g. King et al 2010;Wu et al 2011) and Appendix 7.1 for a more detailed discussion).…”
Section: Discussion On Time-series Analysis and Time-series Lengthmentioning
confidence: 99%
“…Observations of glacial isostatic adjustment (e.g. King et al, 2010) are hard to explain without having viscoelastic relaxation occurring at some depths within the earth, and lab experiments of rock properties also predict that viscoelastic relaxation mechanisms should be important for the deformation we see in the earthquake deformation cycle (Burgmann and Dresen, 2008).…”
Section: Models Of Earthquake Cycle Deformationmentioning
confidence: 99%